2022
DOI: 10.1002/ctm2.949
|View full text |Cite
|
Sign up to set email alerts
|

When the clock ticks wrong with COVID‐19

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) is a member of the coronavirus family that causes the novel coronavirus disease first diagnosed in 2019 (COVID‐19). Although many studies have been carried out in recent months to determine why the disease clinical presentations and outcomes can vary significantly from asymptomatic to severe or lethal, the underlying mechanisms are not fully understood. It is likely that unique individual characteristics can strongly influence the broad disease varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 299 publications
(594 reference statements)
0
5
0
Order By: Relevance
“…The causality of alteration to circadian rest-activity rhythms is unknown and is beyond the scope of this study. However, the circadian rest-activity rhythm may be affected due to the regulatory effect of the circadian clock over physiological functions in the human body such as respiratory function, immune system behavioral aspects, and the metabolic system [52]. In turn, owing to massive infection by pathogenic entities such as SARS-COV-2, these physiological functions are exhibited with alterations after ICU discharge [20,53].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The causality of alteration to circadian rest-activity rhythms is unknown and is beyond the scope of this study. However, the circadian rest-activity rhythm may be affected due to the regulatory effect of the circadian clock over physiological functions in the human body such as respiratory function, immune system behavioral aspects, and the metabolic system [52]. In turn, owing to massive infection by pathogenic entities such as SARS-COV-2, these physiological functions are exhibited with alterations after ICU discharge [20,53].…”
Section: Discussionmentioning
confidence: 99%
“…In turn, owing to massive infection by pathogenic entities such as SARS-COV-2, these physiological functions are exhibited with alterations after ICU discharge [20,53]. Indeed, Papagerakis et al (2022) suggested potential connections between circadian rhythms, clock genes, and SARS-CoV-2 [52]. The additional analysis did not show any significant improvement in sleep and circadian rest-activity rhythm between the evaluated time points; such results may suggest that the effects of hospitalization and the acute phase of the disease are not the responsible for the sleep and circadian alterations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It receives time information from internal photosensitive retinal ganglion cells (ipRGCs) and is further transmitted through the retinohypothalamic tract (RHT) to ensure its synchronization to light/dark changes during the day [2,3] . Rhythm misalignment has been shown to increase the risk of metabolic syndrome [4] , cardiovascular disease [5] , cancer [6][7][8] , and even COVID-19 [9] .…”
Section: Introductionmentioning
confidence: 99%